The Hematopoietic Bone Marrow Niche Ecosystem - Fröbel, Julia; Landspersky, Theresa; Percin, Gülce; Schreck, Christina; Rahmig, Susann; Ori, Alessandro; Nowak, Daniel; Essers, Marieke; Waskow, Claudia; Oostendorp, Robert A. J. (Frontiers in Cell and Developmental Biology, 2021)
The bone marrow (BM) microenvironment, also called the BM niche, is essential for the maintenance of fully functional blood cell formation (hematopoiesis) throughout life. Under physiologic conditions the niche protects hematopoietic stem cells (HSCs) from sustained or overstimulation. Acute or chronic stress deregulates hematopoiesis and some of these alterations occur indirectly via the niche. Effects on niche cells include skewing of its cellular composition, specific localization and molecular signals that differentially regulate the function of HSCs and their progeny. Importantly, while acute insults display only transient effects, repeated or chronic insults lead to sustained alterations of the niche, resulting in HSC deregulation. We here describe how changes in BM niche composition (ecosystem) and structure (remodeling) modulate activation of HSCs in situ. Current knowledge has revealed that upon chronic stimulation, BM remodeling is more extensive and otherwise quiescent HSCs may be lost due to diminished cellular maintenance processes, such as autophagy, ER stress response, and DNA repair. Features of aging in the BM ecology may be the consequence of intermittent stress responses, ultimately resulting in the degeneration of the supportive stem cell microenvironment. Both chronic stress and aging impair the functionality of HSCs and increase the overall susceptibility to development of diseases, including malignant transformation. To understand functional degeneration, an important prerequisite is to define distinguishing features of unperturbed niche homeostasis in different settings. A unique setting in this respect is xenotransplantation, in which human cells depend on niche factors produced by other species, some of which we will review. These insights should help to assess deviations from the steady state to actively protect and improve recovery of the niche ecosystem in situ to optimally sustain healthy hematopoiesis in experimental and clinical settings.